Perilaku Nyamuk Anopheles sp., Vektor Penyakit Malaria di Pulau Lembeh, Kota Bitung, Sulawesi Utara - Jane Tahulending; Paul Kawatu; Woodford Joseph (Universitas Sam Ratulangi, 2024)
Malaria is an infectious disease still health problem, especially in eastern Indonesia. The Ministry of Health targets by 2030, Indonesia will achieve malaria-free areas starting from district/city level to provincial level. The Bitung City Government strongly supports this program, so that elimination efforts are increasingly focused on areas with high cases, namely Lembeh Island. Factors such as topographic conditions with hilly areas surrounded by sea, tropical climate, high rainfall, and lots of standing water create an ideal habitat for the breeding of Anopheles sp. Based on the malaria information system report, the incidence reached 95 cases (2022) and 32 cases (2023). The research aims to analyze the behavior of Anopheles sp. The research used qualitative analysis with secondary data from BTKLPP Class I Manado (2023). Anopheles subpictus is the dominant species (91.62%) which actively sucks blood inside and outside the house. There was no significant relationship between vector density and temperature (P = 0.147) and air humidity (P = 0.233). 36.79% of the area has potential to become receptive Pasir Panjang, Pamurutan and Ketang. The behavior of A. subpictus, very important in determining appropriate vector control methods.